2005
DOI: 10.1038/sj.onc.1208867
|View full text |Cite
|
Sign up to set email alerts
|

Absence of mutation in the putative tumor-suppressor gene KLF6 in colorectal cancers

Abstract: The KLF6 gene encodes the Kru¨ppel-like factor 6, a transcription factor that has been individualized as a tumor-suppressor gene involved in the regulation of cell proliferation and differentiation. Recently, high frequency (42%) of KLF6 mutations have been reported in colorectal cancers (CRC) as in prostate cancers, astrocytic gliomas and hepatocellular carcinomas. The aims of the study was to confirm the frequency of KLF6 mutations in a larger series of CRC than that previously published by using DNA extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 30 publications
1
33
1
Order By: Relevance
“…The Kr€ uppel-like factor 6 (KLF6) gene is a tumor suppressor that is deregulated and inactivated by gene loss or somatic mutation in various cancers, such as colorectal cancer (6), prostate cancer (7), and glioblastoma (8). Our previous tissue profiling results indicated that KLF6 was significantly downregulated in metastatic specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The Kr€ uppel-like factor 6 (KLF6) gene is a tumor suppressor that is deregulated and inactivated by gene loss or somatic mutation in various cancers, such as colorectal cancer (6), prostate cancer (7), and glioblastoma (8). Our previous tissue profiling results indicated that KLF6 was significantly downregulated in metastatic specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with the other studies, they only analyzed exon 2. None of the other studies included methods to [10][11][12][13] (ranging between 0 and 15%) and colorectal carcinoma [14][15][16][17][18] (ranging between 0 and 44%). Similar to prostate cancer, the first studies conducted on these other tumors indicated a high frequency of mutation, but this was not reproduced in subsequent reports.…”
Section: Discussionmentioning
confidence: 99%
“…9 The reported frequency of KLF6 mutations in different types of human cancer varies in the different published studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In prostate cancer, four studies have analyzed the frequency of KLF6 mutations. 6,[30][31][32] In the first published study, Narla et al 6 showed a very high frequency, 55%, whereas in the following study, Chen et al 30 obtained a lower frequency, around 15%.…”
mentioning
confidence: 99%
“…17 However, the extent of KLF6 loss in major human cancers has been recently subjected to passionate debate. Numerous studies now report the absence of somatic mutation nor KLF6 inactivation in colorectal carcinoma, 27 in glioblastomas, 28 in prostate cancer, 29,30 in meningiomas, 28,31 in astrocytic tumors, 32 and, finally, in HCC. 18 Here, we confirmed that KLF6 is not mutated, and expressed in HCC samples, and in HCC-derived cell lines.…”
Section: Discussionmentioning
confidence: 99%